2018
DOI: 10.2196/10143
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of 12-Month Usage Patterns for Two Smoking Cessation Websites: Exploring How Users Engage Over Time

Abstract: BackgroundLittle is known about how individuals engage with electronic health (eHealth) interventions over time and whether this engagement predicts health outcomes.ObjectiveThe objectives of this study, by using the example of a specific type of eHealth intervention (ie, websites for smoking cessation), were to determine (1) distinct groups of log-in trajectories over a 12-month period, (2) their association with smoking cessation, and (3) baseline user characteristics that predict trajectory group membership… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 35 publications
6
25
0
Order By: Relevance
“…Notably, although quitSTART was designed for teens, by Visit 2 it was perceived positively based on the qualitative feedback and a high level of engagement among these young adults with SMI. Given the acceptable perceived usability at the second visit, the much higher level of engagement with quitSTART, and previous work demonstrating the importance of engagement to cessation outcomes [25][26][27], our findings suggest that quitSTART may be a reasonable choice for use among young adult smokers with SMI, particularly if support and coaching facilitate initial use of the app.…”
Section: Principal Findingsmentioning
confidence: 60%
See 2 more Smart Citations
“…Notably, although quitSTART was designed for teens, by Visit 2 it was perceived positively based on the qualitative feedback and a high level of engagement among these young adults with SMI. Given the acceptable perceived usability at the second visit, the much higher level of engagement with quitSTART, and previous work demonstrating the importance of engagement to cessation outcomes [25][26][27], our findings suggest that quitSTART may be a reasonable choice for use among young adult smokers with SMI, particularly if support and coaching facilitate initial use of the app.…”
Section: Principal Findingsmentioning
confidence: 60%
“…Comparison of user engagement data among studies can be challenging because of different durations of follow-up, varied measurements of app engagement (eg, app openings, days of use, and specific actions within the app), and previously demonstrated decay in the use of eHealth interventions over time [ 25 ]. Nevertheless, our QuitGuide findings appear similar to those from other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the more than hundred-odd smokers I have interviewed over the past decade, the vast majority describe their consumption in relation to the packet, rather than how many cigarettes they actually smoke, with the most common category being "a pack a day". Interestingly, the category of the pack-a-day-smoker has now become so naturalized that it's often used in tobacco control accounts as a measure of smoking intensity (for a recent example, see Bricker et al, 2018), with very little reflection on what this actually means. However, while 'typical' packets often contain 20 cigarettes, packs of 10, 25, 30, 40 and 50 are also widely available, depending on the country.…”
Section: Cigarettes Packets and Smokers: Matter Mattersmentioning
confidence: 99%
“… 24 A secondary data analysis found that WebQuit users categorized as “high engagers” (on the basis of a single engagement indicator—logins) saw larger increases in the acceptance of physical cravings at a 3-month follow-up (the only measured theoretical mechanism of action of the intervention) and increased chances of quit success at a 12-month follow-up compared with “low engagers.” 24 In a secondary analysis of the total duration of engagement with WebQuit, three distinct groups were identified, with 5- and 52-week users having greater odds of quit success compared with 1-week users. 25 However, we currently lack knowledge as to how users engage with WebQuit’s features over time and in what order, and whether particular temporal, content-based engagement trajectories are associated with improved cessation outcomes. Although analyses of single engagement indicators (e.g., the frequency of logins) are perhaps considered more efficient than those combining multiple indicators, the former are not suited to addressing whether engagement with particular content over time is associated with outcomes of interest.…”
Section: Introductionmentioning
confidence: 99%